Fundamental Concepts of Architecture : The Vocabulary of Spatial Situations - Janson, Alban; Tigges, Florian (Birkhäuser, 2014)
This dictionary provides a vocabulary that allows the architecture discourse to go beyond the declaration of constructive relationships or the description of architectonic forms in familiar terms like "roof," "base," "wall," and "axis" or "proportion". The point is to describe the experience of architecture: how exactly does it contribute to the experience of a situation?